Malignant Uterine Neoplasms Attended at a Brazilian Regional Hospital: 16-years Profile and Time Elapsed for Diagnosis and Treatment - Elaine Cristina Candido; Nelio Neves Veiga Junior; Monique Possari Minari; Maria Carolina Szymanski Toledo; Daniela Angerame Yela; Julio Cesar Teixeira (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective The present study aims to evaluate the profile of endometrial carcinomas and uterine sarcomas attended in a Brazilian cancer center in the period from 2001 to 2016 and to analyze the impact of time elapsed fromsymptoms to diagnoses or treatment in cancer stage and survival. Methods This observational study with 1,190 cases evaluated the year of diagnosis, age-group, cancer stage and histological type. A subgroup of 185 women with endometrioid histology attended in the period from 2012 to 2017 was selected to assess information about initial symptoms, diagnosticmethods, overall survival, and to evaluate the influence of the time elapsed from symptoms to diagnosis and treatment on staging and survival. The statistics used were descriptive, trend test, and the Kaplan- Meier method, with p-values < 0.05 for significance. Results A total of 1,068 (89.7%) carcinomas (77.2% endometrioid and 22.8% nonendometrioid) and 122 (10.3%) sarcomas were analyzed, with an increasing trend in the period (p < 0.05). Histologies of non-endometrioid carcinomas, G3 endometrioid, and carcinosarcomas constituted 30% of the cases. Non-endometrioid carcinomas and sarcomas weremore frequently diagnosed in patients over 70 years of age and those on stage IV (p < 0.05). The endometrioid subgroup with 185 women reported 92% of abnormal uterine bleeding and 43% diagnosis after curettage. The average time elapsed between symptoms to diagnosis was 244 days, and between symptoms to treatment was 376 days, all without association with staging (p = 0.976) and survival (p = 0.160). Only 12% of the patients started treatment up to 60 days after diagnosis. Conclusion The number of uterine carcinoma and sarcoma cases increased over the period of 2001 to 2016. Aggressive histology comprised 30% of the patients and, for endometrioid carcinomas, the time elapsed between symptoms and diagnosis or treatment was long, although without association with staging or survival.